Degradation-Safety Analytics in Lithium-Ion Cells and Modules: Part III. Aging and Safety of Pouch Format Cells. Issue 11 (2nd November 2021) - Juarez-Robles, Daniel; Azam, Saad; Jeevarajan, Judith A.; Mukherjee, Partha P.
Abstract : Owing to their versatility in cell formats, lithium-ion cells are widely used in energy storage systems. The pouch format cell architecture allows easy adaptability to a manufacturer's application needs. This study aims to characterize the interplay between cycle life aging and off-nominal conditions. Single pouch cells aged to different capacity fade (CF) levels and modules aged to 20% CF were subjected to overcharge tests. Fresh cells and fresh and aged modules were subjected to external short tests. Under overcharge conditions, fresh cells experienced thermal runaway under 1C overcharge but exhibited only swelling under C/3. Overcharged cells with 10% CF experienced swelling and thermal runaway, while cells with over 15% CF experienced swelling and venting through pouch sidewall rupture. It can be conjectured that cells with over 15% CF did not experience thermal runaway due to the relative loss of active material. Under external short, single cells exhibited slight swelling, charring of the anode tab and crumbling of the cathode. Fresh and aged modules subjected to C/3 overcharge experienced catastrophic thermal runaway. Although aging slightly delays the onset of thermal runaway, the fresh module went into catastrophic thermal runaway under external short, whereas the aged one did not.